Determinan Tax Avoidance dengan Komisaris Independen sebagai Variabel Moderating - Lestari, Reza; Tarmizi, Muhammad Irfan (JABI (Jurnal Akuntansi Berkelanjutan Indonesia), 2023)
This study aims to see the influence of political connections, transfer pricing, and sales growth on tax avoidance with an independent commissioner as a moderating variable. The type of data in this study is secondary data with a population of all food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange in 2017-2021. The sampling used purposive sampling, in which 13 companies were selected with 5 years of research so that there were 65 observational data. The analysis used is the structural inquiry model of the partial least square approach (SEM PLS) with the help of Smart PLS 3.0 software. The results of the study concluded that political connections had a positive and significant effect on tax avoidance. Transfer pricing and sales growth have a positive and insignificant effect on tax avoidance. Independent commissioners cannot moderate the relationship between political connections, transfer pricing, and sales growth on tax avoidance.